A Novel Team-Based Learning Approach for an Internal Medicine Residency: Medication-Assisted Treatments for Substance Use Disorders - Daniel Matassa; Benjamin Perrella; Mirela Feurdean (MedEdPORTAL, 2021)
Introduction It is estimated that approximately one-tenth of the US population suffers from substance use disorders (SUD), a problem that is compounded when one considers the impact that drug addiction could have on treatment outcomes for many other chronic diseases. Thus, addiction medicine has become an important component of many successful urban primary care practices and residencies across the country. Our program sought to improve the confidence of our residents in managing SUD by instituting a team-based learning (TBL) activity that focused on the diagnosis and medication-assisted treatment of these illnesses. Methods The class of 80 internal medicine residents were divided into groups of approximately 16 residents, and during the TBL sessions further divided into teams of three to four. Each TBL session consisted of an individual readiness assurance test, a group discussion of the correct answers, and a PowerPoint-based team application activity. Surveys were conducted for each group to assess the residents' attitudes after completing the activity. Results Of residents, 69 of 80 completed the survey. The response to the TBL exercise was overwhelmingly positive, with most residents in agreement that the activity increased their knowledge and confidence in diagnosing and treating patients with SUD. Discussion Overall, this TBL activity was well received by the residents and subjectively increased their competence in managing patients with SUD. In addition, our modification to the traditional TBL format suggested that the theories and spirit behind TBL can be successfully adapted to meet the challenges and intricacies of internal medicine residency education.